2023
DOI: 10.3390/cancers15061705
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Testing Using Next-Generation Sequencing in the Clinical Management of Patients with Non-Small Cell Lung Cancer in a Public Healthcare Hospital

Abstract: Next-generation sequencing (NGS) is a molecular approach able to provide a comprehensive molecular profile of non-small cell lung cancer (NSCLC). The broad spectrum of biomarker-guided therapies has positioned molecular diagnostic laboratories as a central component of patient clinical management. Here, we show the results of an UNE-EN ISO 15189:2022 NGS-accredited assay in a cohort of 350 patients. TP53 (51.0%), KRAS (26.6%) and EGFR (12.9%) were the most frequently mutated genes. Furthermore, we detected co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(59 reference statements)
1
4
0
Order By: Relevance
“…reported the integration of NGS studies (350 patients) into a Spanish reference public healthcare hospital, founding that TP53 (51.0%), KRAS (26.6%), and EGFR (12.9%) were the most frequently mutated genes. Moreover, they found that actionable genetic alterations were significantly more frequent in never‐smokers (87.7%, p < 0.001), 22 as we have found in our study. Also, in study of Sorin et al 24 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…reported the integration of NGS studies (350 patients) into a Spanish reference public healthcare hospital, founding that TP53 (51.0%), KRAS (26.6%), and EGFR (12.9%) were the most frequently mutated genes. Moreover, they found that actionable genetic alterations were significantly more frequent in never‐smokers (87.7%, p < 0.001), 22 as we have found in our study. Also, in study of Sorin et al 24 .…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, this is the largest cohort‐level study in Spain to profile the analyses of cancer biopsy samples using NGS in routine clinical practice. The recent study published by Simarro et al 22 . evaluated the implementation of NGS for lung cancer biopsy samples in routine clinical practice, 22 in contrast to our study which analyzed biopsy samples of another cancer in addition to lung cancer, using NGS routinely.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations